The role of family in the formation of learning motivation for adolescents (Texas Journal of Multidisciplinary Studies, 2022)
This article focuses on the role of family in the formation of learning motivation for adolescents and its family-related aspects. Attempts have been made to reveal specific social and psychological reasons that need to be taken into account in the process of shaping learning motivation in the parent-child relationship.